SPILLWAY DESIGN AND EMERGENCY ACTION PLAN FOR TANJU DAM IN DOMPU REGENCY, WEST NUSA TENGGARA - Carrina
Tanju dam with its 19.43 km2 watershed area is a dam in West Nusa Tenggara, which one of its main purpose is to maximize the water supply in that area. One of Tanju dam main components is the spillway, which serves to spill excess water so it will not exceed the design capacity that could potentially damage the dam. The spillway is 116.43 m long from flow guide channel to stilling basin. In case there is a potential of dam break that is caused by earthquake, an Emergency Action Plan is required to minimize losses through ensuring the safety of life and property. Flood hydrograph modeling caused by dam break is modeled with HEC-HMS resulting the rapidest dam break is caused by overtopping with peak discharge og 10,272.20 m3/s. Flood inundation map modeling is modeled with HEC-RAS with inundation area caused by overtopping is 538.75 ha. The inundation map is then used to determine hazard zone on the flood inundation area and to construct evacuation map.